Realising the Carbon Benefits of Sustainable Land Management Practices: Guidelines for Estimation of Soil Organic Carbon in the Context of Land Degradation Neutrality Planning and Monitoring - Chotte, J.L.; Aynekulu, Ermias; Cowie, A.; Campbell, E.; Vlek, P.; Lal, R.; Kapović-Solomun, M.; Maltitz, G. von; Kust, G.; Barger, N.; Vargas, R.; Gastrow, S. (United Nations Convention to Combat Desertification, 2019)
Land degradation is one of the threats to human and natural systems. Fortunately, over the past few decades awareness of this challenge has grown, and 122 countries have committed to setting land degradation neutrality (LDN) targets, of which 84 have officially validated their targets, and 51 have put their targets into legislation. In this concept, LDN is achieved if new degradation is balanced by reversal of degradation elsewhere in the same land type by restoration or rehabilitation. The primary instrument for achieving LDN is through the implementation of sustainable land management (SLM) practices.